Outcome of bone recycling using liquid nitrogen as bone reconstruction procedure in malignant and recurrent benign aggressive bone tumour of distal tibia: A report of four cases - Eka Wiratnaya I Gede; Arrisna Artha Ida Ayu; Yudhi Setiawan I GN; Wien Aryana IGN; Suyasa I Ketut; Siki Kawiyana I Ketut; Astawa Putu (Journal of Orthopaedic Surgery, 2017)
Amputation still considered as primary choice of malignancy treatment in distal tibia. Bone recycling with liquid nitrogen for reconstruction following resection of malignant bone tumours offers many advantages. We presented four patients with osteosarcoma, Ewing sarcoma, adamantinoma and recurrent giant cell tumour over distal tibia. All of the patients underwent wide excision and bone recycling using liquid nitrogen as bone reconstruction. The mean functional Musculoskeletal Tumor Society (MSTS) score was 75% with no infection and local recurrent. The reconstruction provides good local control and functional outcome.